Varicella Presentation in Adult: A Case Report - Jesryn Dhillon; Dina Arwina Dalimunthe (Indonesian Journal of Global Health Research, 2025)
Varicella is a disease caused by the varicella-zoster virus (VZV), a herpesvirus specific to humans. It is highly contagious but preventable through vaccination. It is usually diagnosed clinically and is often self-limiting. However, complications can include pneumonia, neurological, hematologic, ocular, renal, hepatic conditions, as well as sepsis, and secondary infections that can be fatal. Effective antiviral therapy has reduced associated morbidity and mortality. To report a case of varicella with bronchopneumonia in an adult patient. A 58-year-old male presented with persistent vesicular eruptions on the face, chest, back, and extremities. He was admitted to the emergency room and referred to dermatology. He had no history of prior varicella or vaccination. He was diagnosed with varicella with pneumonia and treated with acyclovir, cetirizine, paracetamol, and fusidic acid cream. Data were obtained through anamnesis, physical examination, and relevant supporting investigations, then qualitatively analyzed by correlating clinical findings and investigation results to confirm the diagnosis, evaluate treatment response, and construct the case narrative. Adult varicella is up to 25 times more severe than in children. The virus is transmitted via the respiratory tract with an incubation period of 10–21 days. Physical stress and disruption of circadian rhythms may impair immune response. Lesions typically start on the face and scalp and spread to the body. A This case highlights a presentation of adult varicella with systemic involvement. Early antiviral treatment can improve prognosis.